A high-strength ecological and environmentally friendly permeable brick and its preparation method

By using special adhesives and appropriate raw materials in permeable bricks, the problem of insufficient permeability and wear resistance of existing permeable bricks is solved, and ecological and environmentally friendly permeable bricks with high strength, good permeability and wear resistance is achieved. .

CN119306449BActive Publication Date: 2025-02-25SHANDONG ZHAOHE ENVIRONMENTAL PROTECTION BUILDING MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411846934.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-25
Estimated Expiration
2044-12-16

AI Technical Summary

Technical Problem

The existing urban pavement paving materials are mainly non-permeable materials, which leads to weak penetration capacity of urban pavement and is prone to trigger urban waterlogging and heat island effects. The existing permeable bricks have shortcomings in water permeability and wear resistance.

Method used

A high-strength ecological and environmentally friendly permeable brick is used, and its raw materials include quartz sand, cement, deionized water, fillers, defoamers and special adhesives. The adhesive is prepared through a multi-step reaction and contains a large amount of oxidized functional groups and hydrophilic functional groups, which improves the adhesion and hydrophilicity.

Benefits of technology

It achieves high strength, good water permeability and wear resistance, can effectively reduce the water problem on the road area, improve the city's rainfall management capabilities, and also has the characteristics of environmental protection and beauty.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_8
    Figure SMS_8
Patent Text Reader

Abstract

The invention discloses a high-strength eco-friendly permeable brick and a preparation method thereof, and relates to the technical field of permeable bricks. The eco-friendly permeable brick comprises the following raw materials in parts by weight: quartz sand: 80-100 parts, cement: 10-15 parts, deionized water: 30-50 parts, filler: 10-12 parts, defoamer: 2-5 parts, adhesive: 5-10 parts. The invention prepares a first-generation polymer by reacting urotropine and tromethamine, and then the first-generation polymer reacts with isocyanate-2-chloro-6-methylphenyl ester to prepare intermediate 1, and then intermediate 1 is reacted with bisphenol A epoxy resin to prepare intermediate 2, and finally γ-aminopropyltriethoxysilane is grafted onto intermediate 2 to prepare adhesive. The eco-friendly permeable brick prepared by the invention has good mechanical strength, water permeability and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of permeable bricks, and in particular to a high-strength ecological and environmentally friendly permeable brick and a preparation method thereof. Background Art

[0002] With the continuous development of economy and society, various construction projects are constantly put on the agenda, which greatly promotes the pace of urbanization in my country. Sponge city is a new generation of urban rainwater management concept, which means that the city can show good "elasticity" in adapting to environmental changes and responding to natural disasters like a sponge. Good permeability can not only avoid the formation of surface runoff, reduce the amount of surface water collected from hardened non-permeable pavement to the municipal pipe network, but also conserve groundwater. The method of making rainwater penetrate is mainly to use permeable pavement materials to make the urban pavement penetrate naturally, and truly "seep" rainwater from the source. At present, the paving materials for most urban pavement construction in my country are non-permeable materials such as concrete or asphalt. The use of these non-permeable paving materials weakens the permeability of the ground, destroys the ecological balance of nature, and easily causes a series of urban problems such as urban waterlogging and heat island effect. Therefore, it is particularly important to develop a permeable brick with good permeability, compressive strength, wear resistance, anti-slip, environmental protection and beauty.

[0003] A Chinese invention patent with publication number CN113501678A discloses a novel imitation stone ecological permeable brick and a preparation method thereof. The ecological permeable brick comprises a brick body coated with an imitation stone coating on the surface. The raw materials of the brick body comprise the following components in parts by weight: 50-60 parts of aggregate, 15-18 parts of polypropylene, 7-8 parts of unsaturated polyester resin, 1-2 parts of cross-linking agent, 6-8 parts of ceramic waste, 4-5 parts of waste glass, 1-2 parts of fly ash, 3-4 parts of diatomaceous earth, 12 parts of adhesive, and 10-15 parts of water. The permeable brick has good compressive strength, but its water permeability and wear resistance are poor. Summary of the invention

[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-strength ecological and environmentally friendly permeable brick and a preparation method thereof.

[0005] To achieve the above object, the present invention is implemented through the following technical solutions:

[0006] A high-strength eco-friendly water-permeable brick, the eco-friendly water-permeable brick comprising the following raw materials in parts by weight: quartz sand: 80-100 parts, cement: 10-15 parts, deionized water: 30-50 parts, filler: 10-12 parts, defoamer: 2-5 parts, adhesive: 5-10 parts;

[0007] The adhesive is prepared by the following method:

[0008] S1: Deionized water, hexamethylenetetramine, tromethamine, and glacial acetic acid are added to the reactor in sequence, stirred, heated to 65-75°C, reacted for 1-2 hours, cooled to room temperature, separated, the water layer removed, and washed with deionized water for 3 times to obtain a first-generation polymer. The reaction equation is shown as follows:

[0009] ;

[0010] S2: Under nitrogen protection, DMF and 2-chloro-6-methylphenyl isocyanate are added to the reactor in sequence, stirred, heated to 50-70°C, and then the first-generation polymer is slowly added dropwise. After the addition, the catalyst dibutyltin dilaurate is added, and the reaction is carried out for 4-6 hours. After post-treatment, the intermediate 1 is obtained. The reaction equation is shown as follows:

[0011] ;

[0012] S3: Under nitrogen protection, DMSO, bisphenol A epoxy resin, and potassium hydroxide are added to the reactor in sequence, stirred, and heated to 50-60°C, and then intermediate 1 is added, reacted for 8-10 hours, cooled, added with ice water for precipitation, filtered, and recrystallized with petroleum ether three times to obtain intermediate 2, the reaction equation of which is shown as follows:

[0013] ;

[0014] S4: DMF, intermediate 2 and γ-aminopropyltriethoxysilane are added to the reactor in sequence, stirred, heated to 80-120°C, reacted for 4-6h, cooled to 60-80°C, triethylamine was added for neutralization, and the adhesive was obtained by vacuum distillation. The reaction equation is as follows:

[0015] ;

[0016] in, represent:

[0017] ;

[0018] The -OH below M is the -OH in the above formula;

[0019] represent:

[0020] ;

[0021] m and n are natural numbers.

[0022] In the step S1, the mass ratio of deionized water, hexamethylenetetramine, tromethamine and glacial acetic acid is 10:2.5:(1.0-1.2):(0.8-1.0).

[0023] In the step S2, the mass ratio of DMF, 2-chloro-6-methylphenyl isocyanate, first-generation polymer, and dibutyltin dilaurate is 50:(12-18):(4-6):(0.01-0.03).

[0024] In the step S3, the mass ratio of DMSO, bisphenol A epoxy resin, intermediate 1 and potassium hydroxide is 30:(10-15):(5-7):(3-6).

[0025] In the step S4, the feed mass ratio of DMF, intermediate 2 and γ-aminopropyltriethoxysilane is 50:(4-6):(20-30).

[0026] The filler is one of silicon dioxide and diatomaceous earth.

[0027] The defoamer is one of polyether ester defoamer SGR1820 and silicone defoamer SGR1830.

[0028] A method for preparing high-strength ecological and environmentally friendly permeable bricks comprises the following steps:

[0029] (1) Weigh by weight: quartz sand: 80-100 parts, cement: 10-15 parts, deionized water: 30-50 parts, filler: 10-12 parts, defoamer: 2-5 parts, adhesive: 5-10 parts;

[0030] (2) Quartz sand, adhesive and defoaming agent are mixed evenly to obtain a first mixture; then the first mixture, cement, filler and deionized water are mixed and stirred to obtain a second mixture; the second mixture is spread in a mold, and the mold is placed in a pressing machine for vibration pressing to obtain a semi-finished permeable brick; the semi-finished permeable brick is placed in a curing room for static curing for 8 days, and then the mold is removed, and the permeable brick is sprayed with water for humidification curing for 28 days to obtain a high-strength ecological and environmentally friendly permeable brick.

[0031] Due to the adoption of the above technical solution, the beneficial effects of the present invention include:

[0032] (1) The present invention prepares a first-generation polymer by reacting urotropine and tromethamine, then reacts the first-generation polymer with 2-chloro-6-methylphenyl isocyanate to prepare an intermediate 1, then reacts the intermediate 1 with a bisphenol A type epoxy resin to prepare an intermediate 2, and finally γ-aminopropyltriethoxysilane is grafted onto the intermediate 2 to prepare an adhesive.

[0033] (2) The adhesive prepared by the present invention contains a large number of oxidative functional groups, among which the epoxy and hydroxyl groups in the epoxy resin give the resin high reactivity, so that the resin has strong cohesion and adhesion, thereby making the quartz sand have good adhesion with cement and fillers; the benzene ring gives the resin heat resistance and rigidity, and at the same time, the epoxy resin is modified by silane to complement the advantages of the two polymers, and a flexible Si-O bond is introduced inside the epoxy. The Si-O bond can make the polymer chain segment rotate more easily, which can reduce the internal stress of the epoxy resin, thereby greatly improving the fracture toughness of the epoxy resin, so that the prepared permeable brick has good mechanical strength.

[0034] (3) The adhesive prepared by the present invention contains a large amount of hydrophilic functional groups, which can improve the hydrophilicity between the adhesive and various materials. Water can quickly wet the surface of the permeable bricks and seep away, reducing the problem of water accumulation on the road. DETAILED DESCRIPTION

[0035] The invention will be further described below in conjunction with the embodiments, but the invention is not limited to these embodiments.

[0036] Example 1

[0037] Preparation of adhesive:

[0038] S1: 100 g of deionized water, 25 g of urotropine, 10 g of tromethamine, and 8 g of glacial acetic acid were added to the reactor in sequence, stirred, heated to 65°C, reacted for 2 h, cooled to room temperature, separated, the water layer was removed, and washed with deionized water for 3 times (100 g of deionized water each time) to obtain a first-generation polymer;

[0039] S2: Under nitrogen protection, 500g DMF and 120g 2-chloro-6-methylphenyl isocyanate were added to the reactor in sequence, stirred, heated to 50°C, and then 40g of the first-generation polymer was slowly added dropwise (dropwise for 5 minutes). After the addition, 0.1g of the catalyst dibutyltin dilaurate was added, reacted for 6h, and distilled at 50°C under reduced pressure for 2h to obtain intermediate 1;

[0040] S3: Under nitrogen protection, 300 g DMSO, 100 g bisphenol A epoxy resin, and 30 g potassium hydroxide were added to the reactor in sequence, stirred, and heated to 50°C, and then 50 g of intermediate 1 was added, reacted for 10 h, cooled, 500 g of ice water was added for precipitation, filtered, and recrystallized with petroleum ether three times (300 g of petroleum ether was used each time) to obtain intermediate 2;

[0041] S4: 500 g of DMF, 40 g of intermediate 2 and 200 g of γ-aminopropyltriethoxysilane were added to the reactor in sequence, stirred, heated to 80°C, reacted for 6 h, cooled to 60°C, 350 g of triethylamine was added for neutralization, and the adhesive was obtained by reduced pressure distillation at 50°C for 2 h.

[0042] Example 2

[0043] Preparation of adhesive:

[0044] S1: 100 g of deionized water, 25 g of urotropine, 11 g of tromethamine, and 9 g of glacial acetic acid were added to the reactor in sequence, stirred, heated to 70°C, reacted for 1.5 h, cooled to room temperature to separate the layers, removed the water layer, and washed with deionized water for 3 times (100 g of deionized water each time) to obtain a first-generation polymer;

[0045] S2: Under nitrogen protection, 500g DMF and 150g 2-chloro-6-methylphenyl isocyanate were added to the reactor in sequence, stirred, heated to 60°C, and then 50g of the first-generation polymer was slowly added dropwise (dropwise for 5 minutes). After the addition, 0.2g of the catalyst dibutyltin dilaurate was added, reacted for 5h, and distilled under reduced pressure at 55°C for 1.5h to obtain intermediate 1;

[0046] S3: Under nitrogen protection, 300 g DMSO, 125 g bisphenol A epoxy resin, and 45 g potassium hydroxide were added to the reactor in sequence, stirred, and heated to 55°C, and then 60 g of intermediate 1 was added, reacted for 9 h, cooled, 500 g of ice water was added for precipitation, filtered, and recrystallized with petroleum ether three times (300 g of petroleum ether was used each time) to obtain intermediate 2;

[0047] S4: 500 g of DMF, 50 g of intermediate 2 and 250 g of γ-aminopropyltriethoxysilane were added into the reactor in sequence, stirred, heated to 100 °C, reacted for 5 h, cooled to 70 °C, 350 g of triethylamine was added for neutralization, and the adhesive was obtained by reduced pressure distillation at 55 °C for 1.5 h.

[0048] Example 3

[0049] Preparation of adhesive:

[0050] S1: 100 g of deionized water, 25 g of urotropine, 12 g of tromethamine, and 10 g of glacial acetic acid were added to the reactor in sequence, stirred, heated to 75°C, reacted for 1 h, cooled to room temperature to separate layers, removed the water layer, and washed with deionized water for 3 times (100 g of deionized water each time) to obtain a first-generation polymer;

[0051] S2: Under nitrogen protection, 500g DMF and 180g 2-chloro-6-methylphenyl isocyanate were added to the reactor in sequence, stirred, heated to 70°C, and then 60g of the first-generation polymer was slowly added dropwise (dropwise for 5 minutes). After the addition, 0.3g of the catalyst dibutyltin dilaurate was added, the reaction was continued for 4h, and the intermediate 1 was obtained by vacuum distillation at 60°C for 1h.

[0052] S3: Under nitrogen protection, 300 g DMSO, 150 g bisphenol A epoxy resin, and 60 g potassium hydroxide were added to the reactor in sequence, stirred, and heated to 60°C, and then 70 g of intermediate 1 was added, reacted for 8 h, cooled, 500 g of ice water was added for precipitation, filtered, and recrystallized with petroleum ether three times (300 g of petroleum ether was used each time) to obtain intermediate 2;

[0053] S4: 500 g of DMF, 60 g of intermediate 2 and 300 g of γ-aminopropyltriethoxysilane were added to the reactor in sequence, stirred, heated to 120°C, reacted for 4 h, cooled to 80°C, 350 g of triethylamine was added for neutralization, and the adhesive was obtained by reduced pressure distillation at 60°C for 1 h.

[0054] Example 4

[0055] Preparation of eco-friendly permeable bricks:

[0056] S1: Weigh quartz sand (400 g of particle size 2-4 mm, 400 g of particle size 6-10 mm): 800 g, cement: 100 g, deionized water: 300 g, filler (silicon dioxide): 100 g, defoamer (polyether ester defoamer SGR1820): 20 g, adhesive (prepared in Example 1): 50 g;

[0057] S2: Mix quartz sand, adhesive and defoaming agent and stir for 20 minutes to obtain a first mixture; then mix the first mixture, cement, filler and deionized water and stir for 10 minutes to obtain a second mixture; spread the second mixture in a mold, place the mold in a press for vibration pressing, during the vibration pressing process, the pressure is 20MPa, the pressing time is 10s, and the vibration frequency is 60Hz to obtain a semi-finished permeable brick; place the semi-finished permeable brick in a curing room for static curing for 8 days, then remove the mold, and spray the permeable brick for humidification curing for 28 days to obtain a high-strength, ecological and environmentally friendly permeable brick with a size of 200mm×100mm×60mm.

[0058] Example 5

[0059] Preparation of eco-friendly permeable bricks:

[0060] S1: Weigh quartz sand (400 g of particle size 2-4 mm, 500 g of particle size 6-10 mm): 900 g, cement: 125 g, deionized water: 400 g, filler (silicon dioxide): 110 g, defoamer (organic silicon defoamer SGR1830): 35 g, adhesive (prepared in Example 2): 75 g;

[0061] S2: Mix quartz sand, adhesive and defoamer evenly, stir for 20 minutes to obtain a first mixture; then mix the first mixture, cement, filler and deionized water and stir for 10 minutes to obtain a second mixture; spread the second mixture in a mold, place the mold in a press for vibration pressing, during the vibration pressing process, the pressure is 20MPa, the pressing time is 10s, and the vibration frequency is 60Hz to obtain a semi-finished permeable brick; place the semi-finished permeable brick in a curing room for static curing for 8 days, then remove the mold, and spray the permeable brick for humidification curing for 28 days to obtain a high-strength, ecological and environmentally friendly permeable brick with a size of 200mm×100mm×60mm.

[0062] Example 6

[0063] Preparation of eco-friendly permeable bricks:

[0064] S1: Weigh 1000 g of quartz sand (500 g of particle size 2-4 mm, 500 g of particle size 6-10 mm), 150 g of cement, 500 g of deionized water, 120 g of filler (diatomaceous earth), 50 g of defoamer (organic silicon defoamer SGR1830), and 100 g of adhesive (prepared in Example 3);

[0065] S2: Mix quartz sand, adhesive and defoamer evenly, stir for 20 minutes to obtain a first mixture; then mix the first mixture, cement, filler and deionized water and stir for 10 minutes to obtain a second mixture; spread the second mixture in a mold, place the mold in a press for vibration pressing, during the vibration pressing process, the pressure is 20MPa, the pressing time is 10s, and the vibration frequency is 60Hz to obtain a semi-finished permeable brick; place the semi-finished permeable brick in a curing room for static curing for 8 days, then remove the mold, and spray the permeable brick for humidification curing for 28 days to obtain a high-strength, ecological and environmentally friendly permeable brick with a size of 200mm×100mm×60mm.

[0066] Comparative Example 1

[0067] The raw material composition and process of the eco-friendly permeable brick are basically the same as those of Example 5, except that no adhesive is added to the composition.

[0068] Comparative Example 2

[0069] The raw material composition and process of the eco-friendly permeable brick are basically the same as those of Example 5, except that the adhesive is replaced by an equal weight of the intermediate 2 prepared in step S3 of Example 2.

[0070] Comparative Example 3

[0071] The raw material composition and process of the eco-friendly permeable bricks are basically the same as those in Example 5, except that the adhesive is replaced with an equal weight of polyurethane adhesive.

[0072] Comparative Example 4

[0073] The raw material composition and process of the eco-friendly permeable brick are basically the same as those in Example 5, except that the adhesive is replaced by 13 g of intermediate 2 (prepared in step S3 of Example 2) and 62 g of γ-aminopropyltriethoxysilane.

[0074] Comparative Example 5

[0075] The preparation method of ecological and environmentally friendly permeable bricks is:

[0076] S1: Weigh quartz sand (400 g of particle size 2-4 mm, 500 g of particle size 6-10 mm): 900 g, cement: 125 g, deionized water: 400 g, filler (silicon dioxide): 110 g, defoamer (organic silicon defoamer SGR1830): 35 g, adhesive (prepared in Example 2): 20 g;

[0077] S2: Mix quartz sand, adhesive and defoamer evenly, stir for 20 minutes to obtain a first mixture; then mix the first mixture, cement, filler and deionized water and stir for 10 minutes to obtain a second mixture; spread the second mixture in a mold (200mm×100mm×60mm), place the mold in a press for vibration pressing, during the vibration pressing process, the pressure is 20MPa, the pressing time is 10s, and the vibration frequency is 60Hz to obtain a semi-finished permeable brick; place the semi-finished permeable brick in a curing room for static curing for 8 days, then remove the mold, and spray water to humidify the permeable brick for 28 days to obtain a high-strength, ecological and environmentally friendly permeable brick.

[0078] Comparative Example 6

[0079] Ecological permeable bricks are made using the raw material composition and process of Example 5 of the Chinese invention patent with publication number CN113501678A.

[0080] The bisphenol A epoxy resin used in the examples and comparative examples of the present application is of model E51, purchased from Hunan Baling Petrochemical Company; the quartz sand specifications are 2-4mm and 6-10mm, purchased from Inner Mongolia Changfan Quartz Sand Co., Ltd.; the cement is road silicate cement grade 42.5 (codenamed P.R7.5), purchased from Shanxi Excellence Cement Co., Ltd.; the polyether ester defoamer SGR1820 and the silicone defoamer SGR1830 were purchased from Xingrui (Shandong) Environmental Technology Co., Ltd.; the polyurethane adhesive model is K-6502, purchased from Guangdong Evergrande New Materials Technology Co., Ltd.; the diatomaceous earth model is DZ300N, purchased from Linjiang Dayuan Diatomaceous Earth New Material Ecological Environmental Protection Technology Co., Ltd.; the silicon dioxide model is HL-200, purchased from Hubei Huifu Nanomaterials Co., Ltd.

[0081] The eco-friendly permeable bricks prepared in Examples 4-6 of the present application and Comparative Examples 1-6 were tested for compressive strength, flexural strength, wear resistance and water permeability coefficient. The test results are shown in Table 1.

[0082] According to GB / T25993-2010 "Permeable Pavement Bricks and Permeable Road Slabs", permeability coefficient and flexural strength tests were carried out.

[0083] Wear resistance and compressive strength tests were carried out according to JC / T945-2005 "Permeable Bricks".

[0084] Table 1 Permeable brick performance test data table

[0085]

[0086] It can be seen from Table 1 that the eco-friendly permeable bricks prepared in Examples 4-6 of the present application have excellent compressive strength, wear resistance and water permeability coefficient.

[0087] Comparative Example 1 is a comparative example prepared without adding adhesive. It can be seen from the data in Table 1 that its compressive strength is 34.2 MPa, the grinding pit length is 28.6 mm, and the water permeability coefficient is 14.5 mm / s. Compared with Example 5, the compressive strength is 24.6 MPa lower, the wear resistance is poor, the water permeability is poor, and the water permeability coefficient is reduced by 14.4 mm / s.

[0088] The adhesive added to Comparative Example 2 is the intermediate 2 prepared in step S3 of Example 2. It can be seen from Table 1 that without adding silane, the compressive resistance of the prepared permeable brick is 21.9 MPa lower than that of Example 5, the wear resistance is average, and the water permeability is relatively poor.

[0089] The adhesive added in Comparative Example 3 is a polyurethane adhesive. As can be seen from Table 1, its compressive strength is 43.7 MPa and its water permeability coefficient is 19.8 mm / s, indicating that the water permeability of the permeable bricks prepared using the polyurethane adhesive is average.

[0090] The adhesive added to Comparative Example 4 is 13 g of intermediate 2 (prepared in step S3 of Example 2) and 62 g of γ-aminopropyltriethoxysilane. As can be seen from Table 1, its compressive strength is 39.6 MPa, the grinding pit length is 26.1 mm, and the water permeability coefficient is 18.3 mm / s. Its compressive strength and water permeability are poorer than those of Example 5.

[0091] The weight of the adhesive added in Comparative Example 5 is 20 g. It can be seen from Table 1 that its compressive strength is 42.5 MPa, the grinding pit length is 25.4 mm, and the water permeability coefficient is 24.6 mm / s. Compared with Example 5, the compressive strength and water permeability are reduced, indicating that the amount of adhesive added has a certain influence on the performance of the permeable brick. Adding too little adhesive will lead to a decrease in the compressive strength of the permeable brick and a decrease in the water permeability.

[0092] Comparative Example 6 is an ecological permeable brick made with the raw material composition and process in Example 5 of the Chinese invention patent CN113501678A. As can be seen from Table 1, its compressive strength is 47.8MPa, the grinding pit length is 25.9mm, and the permeability coefficient is 13.5mm / s. Compared with the permeable bricks prepared in this application, although its compressive strength is better, its permeability is poor.

[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in the field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A high-strength ecological and environmentally friendly permeable brick, characterized in that: The eco-friendly water-permeable bricks include the following raw materials in parts by weight: Quartz sand: 80-100 parts, Cement: 10-15 parts, Deionized water: 30-50 parts, Filling: 10-12 portions, Defoaming agent: 2-5 parts, Adhesive: 5-10 parts; The adhesive is prepared by the following method: S1: Deionized water, hexamethylenetetramine, tromethamine, and glacial acetic acid were added to the reactor in sequence, stirred, heated to 65-75°C, reacted for 1-2 hours, cooled to room temperature, separated, the water layer was removed, and washed with deionized water for 3 times to obtain a first-generation polymer; S2: Under nitrogen protection, DMF and 2-chloro-6-methylphenyl isocyanate are added to the reactor in sequence, stirred, heated to 50-70°C, and then the first-generation polymer is slowly added dropwise. After the addition, the catalyst dibutyltin dilaurate is added, and the reaction is carried out for 4-6 hours. Intermediate 1 is obtained by post-treatment; S3: Under nitrogen protection, DMSO, bisphenol A epoxy resin, and potassium hydroxide were added to the reactor in sequence, stirred, and heated to 50-60°C, and then intermediate 1 was added to react for 8-10 hours. After cooling, ice water was added to precipitate, filtered, and recrystallized with petroleum ether three times to obtain intermediate 2; S4: DMF, intermediate 2 and γ-aminopropyltriethoxysilane are added to the reactor in sequence, stirred, heated to 80-120°C, reacted for 4-6h, cooled to 60-80°C, triethylamine was added for neutralization, and the adhesive was obtained by distillation under reduced pressure.

2. The high-strength ecological and environmentally friendly permeable brick according to claim 1, characterized in that: In the step S1, the mass ratio of deionized water, hexamethylenetetramine, tromethamine and glacial acetic acid is 10:2.5:(1.0-1.2):(0.8-1.0).

3. The high-strength ecological and environmentally friendly permeable brick according to claim 1, characterized in that: In the step S2, the mass ratio of DMF, 2-chloro-6-methylphenyl isocyanate, first-generation polymer, and dibutyltin dilaurate is 50:(12-18):(4-6):(0.01-0.03).

4. The high-strength ecological and environmentally friendly permeable brick according to claim 1, characterized in that: In the step S3, the mass ratio of DMSO, bisphenol A epoxy resin, intermediate 1 and potassium hydroxide is 30:(10-15):(5-7):(3-6).

5. The high-strength ecological and environmentally friendly permeable brick according to claim 1, characterized in that: In the step S4, the feed mass ratio of DMF, intermediate 2 and γ-aminopropyltriethoxysilane is 50:(4-6):(20-30).

6. The high-strength ecological and environmentally friendly permeable brick according to claim 1, characterized in that: The filler is one of silicon dioxide and diatomaceous earth.

7. The high-strength ecological and environmentally friendly permeable brick according to claim 1, characterized in that: The defoamer is one of polyether ester defoamer SGR1820 and silicone defoamer SGR1830.

8. A method for preparing the high-strength ecological and environmentally friendly permeable brick according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Weigh by weight: quartz sand: 80-100 parts, cement: 10-15 parts, deionized water: 30-50 parts, filler: 10-12 parts, defoamer: 2-5 parts, adhesive: 5-10 parts; (2) Quartz sand, adhesive and defoaming agent are mixed evenly to obtain a first mixture; then the first mixture, cement, filler and deionized water are mixed and stirred to obtain a second mixture; the second mixture is spread in a mold, and the mold is placed in a pressing machine for vibration pressing to obtain a semi-finished permeable brick; the semi-finished permeable brick is placed in a curing room for static curing for 8 days, and then the mold is removed, and the permeable brick is sprayed with water for humidification curing for 28 days to obtain a high-strength ecological and environmentally friendly permeable brick.

Citation Information

Patent Citations

  • Novel stone-like ecological water permeable brick and preparation method thereof

    CN113501678A

  • Water permeable brick prepared from solid waste and preparation method thereof

    CN109694215A

  • High-temperature-resistant anti-corrosion scale inhibitor as well as preparation method and application thereof

    CN116768379A